PENATAAN PELINGGIH KEMULAN MEGUMI PURA MAKSAN UKIR, DESA PAKRAMAN PERASI, DESA PERTIMA, KECAMATAN KARANGASEM, KABUPATEN KARANGASEM - Susanta, I N. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi)
Pura Maksan Ukir is one of nine meanings (the symbol of Dewata Nawa Sanga, emblem sekta / forced / Maksan) in Pakraman Perasi, located at a position north of the village as Stana of Ida Betara Gede Ukir / Betara Lingsir and believed to be the oldest temples related the existence of the village. Overall, the condition of the temple along with pelinggih-pelinggihnya in good condition, except for Pelinggih Kemulan Megumi. Pelinggih Kemulan Megumi is the only building shrines are in good condition, both in terms of layout, architectural aesthetics, as well as construction materials and structures and damaged about 75%. Pelinggih Kemulan Megumi shrine itself is actually the most basic pelinggih, but it is most teben and impressed ignored because mis anderstanding Pengempon Maksan and villages. based on the awareness that pelinggih Kemulan Megumi is the most fundamental, through meeting Maksan decided to make the arrangement on Pelinggih Kemulan Megumi. This process of getting technical assistance from a team of stewards 'Grant Udayana Serving' so it can produce documents related planning is required based on the reference and precise rules. In the process of planning and designing the temple used two concepts, namely: kona tri concept and the concept of Tri Hita Karana is applied at each stage, and ensure that each stage as a process of continuous change.
Keywords: tri kona concept, tri hita karana, change, and sustainable